Chapter 7
The Fundamental Theorem of Calculus





7.2 The Fundamental Theorem of Calculus

7.2.2 The First Half of the Fundamental Theorem:
         Evaluation of Definite Integrals

Our next task is to show that the relationship described in the equation

a b v ( t )   d t = F ( b ) - F ( a )

is not special to velocity-distance calculations but holds for integrals in general. To do this, we consider an approximate solution to the initial value problem

d s d t = v ( t ) ,    `stext[(]atext[)]=0`,

by means of Euler's Method.

Recall that Euler's Method generates a sequence of numbers `s_1`, `s_2`, `s_3`, and so on, that approximates values of `stext[(]t text[)]` at times `t_1`, `t_2`, `t_3`, and so on. Specifically, we can divide the interval `[a,b]` into `n` subintervals by taking `Delta t=text[(]b-atext[)/]n` and choosing the points of subdivision to be

  `t_0` `=a`,
  `t_1` `=a+Delta t`,
  `t_2` `=a+2 Delta t`,
  `t_3` `=a+3 Delta t`,

and so on, up to

   
  `t_n` `=b`.

Then, for `k=1, 2, ... , n`, [starting with `s_0=stext[(]0 text[)]=0`], each `s_k` is generated from the previous one by the "rise `=` slope `times` run" formula:

s k = s k - 1 + v ( t k - 1 ) Δ t .

To make the connection between the Euler's Method approximate solution to the initial value problem and the definite integral in

a b v ( t )   d t = F ( b ) - F ( a ) ,

we write out explicitly the values of the `s_k`'s:

  `s_1=s_0+vtext[(]t_0 text[)]Delta t `=vtext[(]t_0 text[)]Delta t`,
  `s_2=s_1+vtext[(]t_1 text[)]Delta t` `=vtext[(]t_0 text[)]Delta t+vtext[(]t_1 text[)]Delta t`,
  `s_3=s_2+vtext[(]t_2 text[)]Delta t` `=vtext[(]t_0 text[)]Delta t+vtext[(]t_1 text[)]Delta t+vtext[(]t_2 text[)]Delta t`,

and so on, up to

   
  `s_n=s_(n-1)+vtext[(]t_(n-1) text[)]Delta t` `=vtext[(]t_0 text[)]Delta t+vtext[(]t_1 text[)]Delta t+ cdots +vtext[(]t_(n-1) text[)]Delta t`.

In sigma notation, this last equation is the same as

s n = k = 1 n v ( t k - 1 ) Δ t .

That is, `s_n`, the Euler approximation to `stext[(]t_n text[)]` [which is the same as `stext[(]b text[)]`], is exactly equal to the left-hand sum with `n` terms that approximates the definite integral of `vtext[(]t text[)]` from `a` to `b`.

Now, as `n` becomes large — and the step size `Delta t` becomes small — two things happen to the equation

s n = k = 1 n v ( t k - 1 ) Δ t .

First, the Euler approximation to `stext[(]t text[)]` gets closer and closer to the true solution of the initial value problem

d s d t = v ( t ) ,    `stext[(]atext[)]=0`.

In particular, `s_n` approaches `stext[(]b text[)]`. Second, the sum on the right-hand side approaches the definite integral of `vtext[(]t text[)]` from `a` to `b`. When we consider limiting values, we find

s ( b ) = a b v ( t )   d t .

This observation is not limited to the relationship between distance and velocity. In particular, nowhere in this discussion did we use any particular physical interpretation of the functions `vtext[(]t text[)]` and `stext[(]t text[)]`.

Checkpoint 1Checkpoint 1

We are now ready to examine the relationship between antidifferentiation and the definite integral. Suppose we want to calculate a b f ( t )   d t and we know one antiderivative for `ftext[(]t text[)]` is `Gtext[(]t text[)]`. Then the solution of the initial value problem

d F d t = f ( t ) ,     F ( a ) = 0,

is a function that differs from `Gtext[(]t text[)]` by a constant. That constant might be zero, but all we know for sure is that `Ftext[(]t text[)]=Gtext[(]t text[)]+C` for some constant `C`. Since `Ftext[(]atext[)]=0`, we know that `0=Gtext[(]atext[)]+C`, or `C=-Gtext[(]atext[)]`.

Checkpoint 2Checkpoint 2

The last equation in Checkpoint 2,

a b f ( t )   d t = G ( b ) - G ( a ) ,

is part of the Fundamental Theorem of Calculus. It says that one way to find the value of a definite integral a b f ( t )   d t is to find any antiderivative `Gtext[(]t text[)]` of `ftext[(]t text[)]` and then calculate `Gtext[(]b text[)]-Gtext[(]atext[)]`.

Example 1

Calculate 0 1 t 3   d t .

Solution   We need a function that has `t^3` as its derivative. You already know that one such antiderivative is `t^4text[/]4`. It follows that

0 1 t 3   d t = 1 4 - 0 4 = 1 4 .

Note that we could have used `t^4text[/]4+7` as an antiderivative, in which case the computation would have been

0 1 t 3   d t = ( 1 4 + 7 ) - ( 0 4 + 7 ) = 1 4 .

Of course, if we had used any other antiderivative of `t^3`, the result would end of solutionhave been the same.

Go to Back One Page Go Forward One Page

Contents for Chapter 7